Punctuated invasion of water, ice, snow and terrestrial ecozones by segmented worms (Oligochaeta: Enchytraeidae: Mesenchytraeus) - Lang, Shirley A.; Saglam, Naim; Kawash, Joseph; Shain, Daniel H. (Royal Soc, 2017)
Segmented worms (Annelida) are among the most successful animal inhabitants of extreme environments worldwide. An unusual group of enchytraeid oligochaetes of genus Mesenchytraeus are abundant in the Pacific northwestern region of North America and occupy geographically proximal ecozones ranging from low elevation rainforests and waterways to high altitude glaciers. Along this altitudinal transect, Mesenchytraeus representatives from disparate habitat types were collected and subjected to deep mitochondrial and nuclear phylogenetic analyses. Our data identify significant topological discordance among gene trees, and near equivalent interspecific divergence levels indicative of a rapid radiation event. Collectively, our results identify a Mesenchytraeus 'explosion' coincident with mountain building in the Pacific northwestern region that gave rise to closely related aquatic, ice, snow and terrestrial worms.
Keywords: adaptive; glacier; evolution; discordance; annelid